2021
DOI: 10.31234/osf.io/jz6xe
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Big Role of Authority, Sanctity, and Modern Myths About Sexual Aggression in Blaming the Rape Victims: A Study on Culture of Honor

Abstract: According to Moral Foundation Theory, people rely on five intuitive-based foundations in their moral judgments. These foundations are divided into two clusters: Individualizing foundations (Care and Fairness) and Binding foundations (Loyalty, Authority, and Sanctity). In this study, the authors investigated the relationship between moral foundations and AMMSA with victim-blaming and the moderating role of social desirability in Iranian Culture. Consistent with previous findings, victim-blaming was best predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Most recently, Bagherian Miandoab et al (2021) examined the moral roots of the Acceptance of Modern Beliefs About Sexual Aggression (AMMSA) and victim blaming. They have shown that binding moral foundations predict victim-blaming attitudes in the Iranian sample.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, Bagherian Miandoab et al (2021) examined the moral roots of the Acceptance of Modern Beliefs About Sexual Aggression (AMMSA) and victim blaming. They have shown that binding moral foundations predict victim-blaming attitudes in the Iranian sample.…”
Section: Introductionmentioning
confidence: 99%